QING-QI RICKSHAW: A BOON OR BANE FOR PUBLIC TRANSPORTATION? A STUDY OF ROAD TRAFFIC INJURY PATTERNS INVOLVING QING-QI RICKSHAWS IN KARACHI PAKISTAN - Muzzammil, Muhammad; Minhas, Muhammad Saeed; Effendi, Jahanzeb; Jahanzeb, Syed; Mughal, Ayesha; Qadir, Abdul (Journal of Ayub Medical College Abbottabad, 2017)
Background: The three-wheeler Qing-qi and Compressed Natural Gas (CNG) auto-rickshaws were introduced in Karachi to meet the transportation demand of the growing population. These vehicles have directly or indirectly been implicated in a number of road traffic violations as well as road accidents. This study aims to describe the crash characteristics and injury patterns for Qing-qi rickshaw occupants and other road users hit by Qing-qi rickshaw in Karachi, Pakistan. Methods: An Observational/ Descriptive study was conducted at Accident& Emergency and Orthopaedic Surgery Department, Jinnah Post Graduate Medical Centre, Karachi Pakistan from July 2014 to June 2015.All patients who came with Qing-qi rickshaw accident in Accident& Emergency (A&E) of JPMC were included. Crash characteristics, details of injuries, injury severity parameters and outcome were documented in detailed interviews. Results: Four hundred and eighty-six rickshaw related injuries were noted in road traffic accidents by Qing-gi rickshaw. Age range was 2-85 (43.5±58.68). 350 injured victims were males and 136 were females. By occupation most victims were laborers and daily wage workers (45%) and students (21%). Overloading of vehicle with more than two passengers was found in (28.5%). The most common cause of injury was collision with a moving vehicle (56%), followed by fall from rickshaw. The most common contributing factor was the overloading of rickshaw and roll over on turning (61%). Injury severity on arrival were mild (49%), moderate were (32%), and severe were (19%). Injuries related to head and neck (26%), face (14%), thorax and abdomen (5%), lower extremity and pelvic girdle (31%) and upper extremity (23%) were observed. Conclusion: Qing-qi rickshaw injuries are common and these vehicles are vulnerable to road traffic accidents. Occupants and road users are both at risk of injuries. Keywords: Qing-qi rickshaw; road traffic accidents; trauma; burden; three-wheeler vehicle; injury prevention; engineering; public transport